2006
DOI: 10.3168/jds.s0022-0302(06)72523-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chestnut Tannin on Fermentation Quality, Proteolysis, and Protein Rumen Degradability of Alfalfa Silage

Abstract: Two experiments were conducted on alfalfa to investigate the effects of the addition of commercial chestnut hydrolyzable tannin at ensiling on 1) silage fermentation quality in lab-scale silos and protein degradation in the rumen, and 2) silage fermentation quality and proteolysis in bale silages. Wilted alfalfa was prepared with 4 tannin levels (0, 2, 4, and 6% on a dry matter (DM) basis; T0, T1, T2, T3, respectively) and ensiled in lab-scale silos. Silages (33% DM) were analyzed for fermentation quality, pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
78
4
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(95 citation statements)
references
References 31 publications
10
78
4
3
Order By: Relevance
“…Moreover, the presence of higher content of phenolic compounds and tannins in sorghum silage has been found to be related to the protection of dietary protein, structural carbohydrates and starch against degradation by ruminal microorganisms (Tabacco et al, 2006;Oliveira et al, 2007). In this study, no significant difference was observed in IVDMD and IVOMD for the silage mixtures containing 0%, 20% and 40% of SS.…”
Section: In Vitro Rumen Degradability and Fermentation Of Ss-af Silagmentioning
confidence: 57%
“…Moreover, the presence of higher content of phenolic compounds and tannins in sorghum silage has been found to be related to the protection of dietary protein, structural carbohydrates and starch against degradation by ruminal microorganisms (Tabacco et al, 2006;Oliveira et al, 2007). In this study, no significant difference was observed in IVDMD and IVOMD for the silage mixtures containing 0%, 20% and 40% of SS.…”
Section: In Vitro Rumen Degradability and Fermentation Of Ss-af Silagmentioning
confidence: 57%
“…Tabacco et al . () show that low levels of chestnut HT, applied prior to ensiling lucerne, are useful for reducing proteolysis in silages and could improve protein utilization (with a slight depression of organic matter digestibility).…”
Section: Beneficial Effects On Ruminantsmentioning
confidence: 99%
“…Lactobacillus plantarum is effective in reducing ammonia nitrogen content, while less is known regarding its effects on individual nonprotein nitrogen compounds, protein fractions and proteases activity (Slottner & Bertilsson, ; Wang, Wang, Zhou, & Feng, ). Recent studies reported that using tannin, a phenolic plant secondary metabolite, can modify protein metabolism in silage and in the rumen (Min et al., ; Tabacco et al., ). Chinese gall ( Galla chinensis ) is originated from the abnormal growth of Chinese gallnut ( Rhus chinensis Mill), which is widely distributed in China.…”
Section: Introductionmentioning
confidence: 99%